New interpretation of the Ranunculus cornutus–R. marginatus complex (Ranunculaceae) - Ziffer-Berger, Jotham; Leschner, Hagar V. (Phytotaxa, 2013)
We re-evaluated the morphological variation in the Ranunculus cornutus–R. marginatus complex (Ranunculus sect. Echinella, Ranunculaceae), with a special focus on the Levant. The occurrence of R. marginatus in the Levant is questioned and R. scandicinus should be treated as a variety of R. cornutus. Type material is discussed and descriptions of species are provided.